Cigarette Smoking and Variations in Systemic Immune and Inflammation Markers - Shiels, Meredith S. (Oxford University Press, 2014)
BACKGROUND: A comprehensive characterization of the effects of cigarette smoke on systemic soluble immune/inflammatory markers may provide insight into the mechanisms through which smoking causes disease. METHODS: Levels of 78 inflammation, immune, and metabolic markers were measured using multiplex immune assays in 1819 Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) participants aged 55 to 74 years from three existing nested case-control studies. These data were made representative of the entire PLCO screening arm through reweighting with weights estimated in logistic regression models. We assessed associations between smoking status, cigarettes smoked per day, and time since quitting with dichotomized marker levels using adjusted weighted logistic regression models. RESULTS: Current smoking was associated with 10 inflammation markers after correcting for multiple testing, encompassing several components of the immune/inflammation response. Levels of seven of these markers (interleukin [IL]-15, IL-1RA, IL-1β, IL-16, stem cell factor, soluble interleukin 6 receptor, and soluble vascular endothelial growth factor receptor 3) were lower among current smokers (n = 414) when compared with never smokers (n = 548), with odds ratios (ORs) ranging from 0.44 to 0.27, while levels of CC motif ligand (CCL)/thymus and activation regulated chemokine (CCL17/TARC) (OR = 4.08, 95% confidence interval [CI] = 2.01 to 8.25), CCL11/EOTAXIN (OR = 2.57, 95% CI = 1.45 to 4.55), and C-reactive protein (CRP) (OR = 2.54, 95% CI = 1.29 to 4.98) were elevated. These markers were not associated with cigarettes per day among current smokers, but there were trends in IL-15, IL-1RA, IL-1β, CCL17/TARC, CCL11/EOTAXIN, and CRP levels across categories of years since quitting smoking. CONCLUSIONS: Smoking is associated with a broad range of alterations in systemic immune and inflammation marker levels among older, long-term smokers. Smoking cessation may result in marker levels reverting back to those of never smokers over time.